2013
DOI: 10.1152/ajpgi.00257.2013
|View full text |Cite
|
Sign up to set email alerts
|

Peristalsis and propulsion of colonic content can occur after blockade of major neuroneuronal and neuromuscular transmitters in isolated guinea pig colon

Abstract: We recently identified hexamethonium-resistant peristalsis in the guinea pig colon. We showed that, following acute blockade of nicotinic receptors, peristalsis recovers, leading to normal propagation velocities of fecal pellets along the colon. This raises the fundamental question: what mechanisms underlie hexamethonium-resistant peristalsis? We investigated whether blockade of the major receptors that underlie excitatory neuromuscular transmission is required for hexamethonium-resistant peristalsis. Video im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…50 The same group recently reported that propagation velocities are significantly reduced, but not abolished, in the presence of hexamethonium. 51 These suggest that nicotinic receptors are partially involved in the regulation of peristalsis of the guinea pig distal colon. It seems that the contribution of nicotinic receptors to colonic peristalsis might depend upon experimental procedures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…50 The same group recently reported that propagation velocities are significantly reduced, but not abolished, in the presence of hexamethonium. 51 These suggest that nicotinic receptors are partially involved in the regulation of peristalsis of the guinea pig distal colon. It seems that the contribution of nicotinic receptors to colonic peristalsis might depend upon experimental procedures.…”
Section: Discussionmentioning
confidence: 98%
“…29,36,49 In contrast, others demonstrated that nicotinic receptors are not essential in mediating peristalsis of the guinea pig distal colon. 50,51 They showed that hexamethonium temporarily arrested peristalsis and fecal pellet propulsion. However, if time was allowed for the pellet to remain in the oral end of the colon, the pellet gradually propelled anally, until finally being expelled.…”
Section: Discussionmentioning
confidence: 99%
“…Video recording and spatiotemporal mapping of intestinal and colonic segments have been applied to a variety of species including zebrafish 26 , mouse 25,[27][28][29][30] , rat 7,9,[30][31][32][33] , guinea pig 5,6,8,[13][14][15][16][17][18][19]24,30,32,34,35 , brushtail possum 12,36 , rabbit 2,30,37,38 , chicken 39 , pig 40,41 and human 42 . The most widely studied species is the guinea pig.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of STmaps and analysis of changes in motility pattern have been applied to key questions in the gastrointestinal motility of intestine and colon. These include: differentiation of neurogenic and myogenic contractions and defining the role of interstitial cells of Cajal 6,9,11,12,16,24,26,27,[29][30][31]33,[37][38][39][40]42 , understanding the complex interactions between the circular and longitudinal muscle layers 2,7,8,11,12,32,39,40 , examining the effects of intraluminal nutrients 10,18,19 , microbial strains 34 , and viscosities 12,36 on various motility patterns, and understanding the role of various endogenous neurohormonal agents and exogenous pharmacological agents 2,[4][5][6][7]9,10,[13][14][15][16][17]28,35,40 in the generation and modification of motility...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation